Pengembangan Modul Inventory Management pada Aplikasi Master Distribution Centre System Menggunakan Framework Flask di PT XYZ - Andre Josiah Budianto; Pratyaksa Ocsa Nugraha Saian (KITA Institute, 2023)
PT XYZ is a retail business with over 15,000 outlets. Along with the development of information technology, every retail business must adapt to existing technological developments, including PT XYZ which requires new technology. PT XYZ already has inventory management system, but the system continues to increase operating costs every year. Therefore, PT XYZ needs to replace the old inventory management system with a web-based system using the Flask framework to reduce operating costs that continue to grow. This research was conducted in 4 stages, namely analysis stage, design stage, coding stage and testing stage. The result of this research is inventory management module built using the Flask framework and information related to developing inventory management module. Based on the research conducted, an inventory management module was produced where this module successfully met the business needs as evidenced by the results of the Black Box tests and User Acceptance Tests performed.